Spill The Tea, Not The Smoke: A Critical Review of Innovative Interventions For The Dual Tobacco And Environmental Crisis in Indonesia - Widyowati, Agustin; Desy Puspita Ayu, Serlyna; Ardilla Sari, Novianti; Aurellia Aurelly, Mayranda; Eurike Mawi; Esdayani Emba Pudang; Shofiyatuzainab (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
The high prevalence of tobacco causes a dual crisis (health and environment) in Indonesia. Currently, tobacco control interventions are only echoed focusing on the dangers of cigarette smoke to health, not touching on the issue of sustainability to environmental impacts. The purpose of the research is to find out the challenges, innovations and strategies in dealing with the tobacco crisis. A systematic literature review using Google Scholar, PubMed, Scopus, and Garuda Portal databases which is limited to published articles from January 2015 – June 2025. The search strategy uses a combination of keywords with Boolean (AND/OR) operators. The search selection uses inclusion and exclusion criteria. The selection process uses the PRISMA guide. A trend of programs that combine digital technology and ecological awareness has been found, but its scalability is still limited. A paradigm shift towards relevant integrated programs for young people is needed to effectively address this crisis.